Presentation matters: Impact of association of amphiphilic LPS with serum carrier proteins on innate immune signaling. - Loreen R Stromberg; Heather M Mendez; Jessica Z Kubicek-Sutherland; Steven W Graves; Nicolas W Hengartner; Harshini Mukundan (PLoS ONE)
Recognition of Pathogen-associated Molecular Patterns (PAMPs) by Toll-like receptors is central to innate immunity. Many bacterial PAMPs such as lipopolysaccharide (LPS) and lipoteichoic acid have amphiphilic properties. The hydrophobicity of amphiphilic PAMPs contributes to increasing entropy and causes these molecules to self-aggregate or bind host carrier proteins in aqueous physiological environments. The goal of this work was to determine how innate immune signaling is impacted by physical presentation and association of amphiphilic PAMPs with serum carrier proteins, using LPS as an example molecule. Specifically, we measured LPS-induced cytokine profiles in murine macrophages when the antigen was presented associated with the various serum carrier proteins in serum versus a serum-depleted system. Our study demonstrates that the observed cytokine profiles are dramatically different when LPS is presented in buffer, versus in serum when it is associated with proteins, specifically with respect to inhibition of pro-inflammatory cytokines in the latter. These studies suggest that LPS-mediated cytokine expression is dependent on its presentation in physiological systems. The amphiphilicity of bacterial PAMPs and consequent association with lipoproteins is a feature, which should be taken into account in the design of in vitro experiments. Further studies of the interdependencies of different serum carriers can identify pathways for drug delivery and diagnostics.